If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 12 = 24x + 36 Reorder the terms: 12 + 8x = 24x + 36 Reorder the terms: 12 + 8x = 36 + 24x Solving 12 + 8x = 36 + 24x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24x' to each side of the equation. 12 + 8x + -24x = 36 + 24x + -24x Combine like terms: 8x + -24x = -16x 12 + -16x = 36 + 24x + -24x Combine like terms: 24x + -24x = 0 12 + -16x = 36 + 0 12 + -16x = 36 Add '-12' to each side of the equation. 12 + -12 + -16x = 36 + -12 Combine like terms: 12 + -12 = 0 0 + -16x = 36 + -12 -16x = 36 + -12 Combine like terms: 36 + -12 = 24 -16x = 24 Divide each side by '-16'. x = -1.5 Simplifying x = -1.5
| x^3=4.2 | | 1/2*4*3/2 | | 2*1*1/4 | | X-6=124 | | 2x+11=39 | | 1/2*1/4*1/3 | | x-x/6=1/3 | | 4/3*3/5*3 | | (4x^4/32x)^3 | | 4x+1=5+2x | | 6x+1=2x+19 | | 9x^2+45x-500=0 | | 85+80+79+82+76+x=81 | | 2x+5=3x+70 | | x+(x+16)+2x=180 | | X/3-3-6=12-8 | | 16-R=7 | | -6a/7=-30 | | k^2+4k-20=0 | | -6x/7=-30 | | 2x+12y=140 | | 5(2c-1)-3=5c+2 | | 5x^2-3xy-8x^2=0 | | 5v+23=10v-17 | | Cos3x=1/2 | | 2x^4+10x^2-72=0 | | z/9-8=2 | | 2x^2+10x^2-72=0 | | 4(5c-1)-3=15c+18 | | 23+2y-5=10y-12-2y | | 3n=5n | | b^3-30n^2+20=0 |